2014
DOI: 10.1159/000357226
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Loss Prevalence and Risk Indicators among 12-Year-Old Schoolchildren from South Brazil

Abstract: This population-based cross-sectional study aimed to assess the prevalence and risk indicators for tooth loss due to dental caries among 12-year-old schoolchildren from South Brazil. 1,528 out of 1,837 (participation rate = 83.17%) schoolchildren were included. Tooth loss prevalence was 5.81% (95% CI = 3.71-8.98) and 0.08 (95% CI = 0.04-0.12) teeth were missing. Schoolchildren with low socioeconomic status (OR = 2.28, 95% CI = 1.23-4.21), who repeated years in school (OR = 1.56, 95% CI = 1.01-2.42), and with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
3
0
2
Order By: Relevance
“…In this study, the number of previously extracted permanent first molars was 128 (2.66%) of 4,816 PFM teeth in 97 (8%) of 1,204 patients. The data were compared with previous studies [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the number of previously extracted permanent first molars was 128 (2.66%) of 4,816 PFM teeth in 97 (8%) of 1,204 patients. The data were compared with previous studies [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Alves et al 16 performed a study among 12-yearold schoolchildren from South Brazil. The researchers observed that tooth loss rate in 1,528 patients were 5.81%.…”
Section: Discussionmentioning
confidence: 99%
“…Alves ve ark. 19 Brezilya'da, 12 yaş grubu çocuklarda diş çürüğüne bağlı diş çekim sıklığını %5.81 olarak tespit etmiştir. George ve ark.…”
Section: Discussionunclassified
“…This sample size far exceeded that needed for an association study investigating caries experience and caries activity (statistical power calculated a posteriori achieved 100% for both predictors). Further details on the sampling strategy and non-response analysis can be found elsewhere [Alves et al, 2014].…”
Section: Methodsmentioning
confidence: 99%